PENDAPATAN DAN EFISIENSI USAHATANI SECARA EKONOMIK VARIETAS PADI BK SITUBONDO 01 AGRITAN DI DESA BATTAL KABUPATEN SITUBONDO - Supriono, Agus; Sisil Annisa, Rofiu; Hasanah, Julita; Purnamasari, Meidiana; Soejono, Djoko; Bastara Zahrosa, Dimas (Jurnal Agriust, 2026)
In line with the national rice productivity enhancement strategy, the Regional Government of Situbondo Regency, East Java Province, has taken an active role in initiating the development of superior rice varieties. In early 2023, Situbondo Regency released a new superior rice variety, Bk Situbondo 01 Agritan, which was developed to support the IP 400 program. In 2024, this superior variety began to be cultivated in several villages, including Battal Village, Panji District, particularly by the Joyo Mulyo 3 Farmer Group. In relation to this initiative, a study was conducted to determine whether the farming of this variety is economically profitable and efficient.The results showed that, economically, the farming of Bk Situbondo 01 Agritan is profitable and efficient. The farming is profitable with an average income of IDR 9,267,039.08 per hectare per planting season. It is also efficient, as every additional IDR 1 spent on production costs yields an additional IDR 1.35 in revenue, or an additional IDR 0.35 in profit. Furthermore, under an economic simulation assuming a 15% decrease in production and price and a 15% increase in variable costs, while keeping other factors constant, the farming remains profitable and efficient.